DEKOLONIALISASI DEMOKRASI DARI PESANTREN SUKOREJO - Azizi (Al'Adalah, 2014)
The issue raised in this paper is about the fenomena of harmony both NU, MD and LDII communities di Awar-Awar Village Asembagus Situbondo Regency. By used ethnography approach founded that harmony constructed in a social manner by NU, MD and LDII communities and elites of Awarawar village in every day life. Social construction con-sists of three moments that is externalization of religious understanding social institution, objectivation through interaction both people by social institution, and internalization is self identification by socialization. In a social manner, because of it pathernalistic character made elites construction influence to people construction. In a social manner, “pendalungan” (Hybrid culture between Java and Madura ethnic) characteristic also give cultural frame to creating harmony. The harmony condition influence all live aspects of people either in a social manner or economy and culture.